Terrorist Deradicalisation Programme in Malaysia: A Case Study / Mohd Norzikri Kamaruddin, Noor Nirwandy Mat Noordin and Abd Rasid Abd Rahman - Kamaruddin, Mohd Norzikri; Mat Noordin, Noor Nirwandy; Abd Rahman, Abd Rasid (Centre for Media and Information Warfare Studies, 2017)
Radicalisation leading to violence has become a growing fear among Malaysians, as terrorism emerged to be one of the main security threats to the stability of the country. Although Malaysia has suffered relatively fewer acts of violence, this fear has intensified and a deradicalisation strategy is needed in the Malaysian context. Hailed as one of the most successful deradicalisation programmes in the world, Malaysia claims some significant degree of success for its deradicalisation programme. As preventive measures, Malaysia adopted the deradicalisation strategy that requires strategic collaboration between the government and religious departments to inhibit extremist threat at home or abroad by individuals or group of individuals. In a qualitative case study methodology, in-depth interviews were conducted with authorities, academicians, and former terrorists to explore solutions to radicalisation. This study proposes a deradicalisation model, known as Wasatiyyah Deradicalisation Model. Many elements seen in deradicalisation programme in Malaysia including module, enforcement, financial, counselling and religious guidance. Policy recommendations and directions for future research are also discussed. With these results, this study hopes to add to the existing, yet limited, knowledge the field has in respect to these types of deradicalisation programmes, and comes at a time when the threats from ISIS affiliated terrorist groups appear to be on the rise